Cross‐Scale Interactions Dictate Regional Lake Carbon Flux and Productivity Response to Future Climate. Issue 15 (1st August 2019) - Zwart, J. A.; Hanson, Z. J.; Read, J. S.; Fienen, M. N.; Hamlet, A. F.; Bolster, D.; Jones, S. E.
Abstract: Lakes support globally important food webs through algal productivity and contribute significantly to the global carbon cycle. However, predictions of how broad‐scale lake carbon flux and productivity may respond to future climate are extremely limited. Here, we used an integrated modeling framework to project changes in lake‐specific and regional primary productivity and carbon fluxes under 21st century climate for thousands of lakes. We observed high uncertainty in whether lakes collectively were to increase or decrease lake CO2 emissions and carbon burial in our modeled region owing to divergence in projected regional water balance among climate models. Variation in projected air temperature influenced projected changes in lake primary productivity (but not CO2 emissions or carbon burial) as warmer air temperatures decreased productivity through reduced lake water volume. Cross‐scale interactions between regional drivers and local characteristics dictated the magnitude and direction of lake‐specific carbon flux and productivity responses to future climate. Plain Language Summary: Primary production in lakes sustains important aquatic food webs, and, collectively, lakes play an important role in the global carbon cycle and contribute substantially to global greenhouse gas dynamics and resulting changes in climate. Primary production in lakes and net carbon emissions are affected by climate change. In this study, we simulated lake carbon dynamics and algae growth for thousands of lakes in response to future climate scenarios. Projected future lake contributions to regional greenhouse gas emissions and algal growth were uncertain because of wide variation in future temperature and precipitation, especially in summer. Local characteristics (e.g., water flow paths and lake water color) dictated how much and in which direction individual lake greenhouse gas emissions and algal growth responded to future climate, highlighting the need for computer simulations that account for interacting effects of regional climate and local characteristics on lake dynamics. Key Points: Future regional water balance dictated variation in regional lake CO2 emissions, carbon burial, and primary productivity Increased air temperature reduced regional lake productivity due to reduced lake volume but had no effect on CO2 emissions or carbon burial Cross‐scale interactions dictated the magnitude and direction of lake‐specific responses to future climate projections